Exercises in quantum field theory:a self-contained book of questions and answers - Atkinson, David; Johnson, Porter Wear (New Delhi: Overseas Press(India) Pvt. Ltd., 2007)
This book is the last in a series of four volumes. It contains the full solutions of all 100 exercises and problems of Volume 2, Quantum Filed Theory: A Self-Contained Course. For the convenience of the user, each question is reproduced in this book, followed immediately by the solution. Beside solving the problem, many of the expositions include additional didactic material. Where feasible, algebraic answers are given; but in some places recourse to approximate methods was necessary. Some of the mumerical results were obtained by using Mathematica (which is a trademark of Wolfram Research Inc), but for readers without access to this system, many numerical answers can be checked by means of a scientific calculator. It cannot be emphasized enough that the temptation for a student to look immediately at the worked-out answers is self-defeating Look at the answers, certainly, but only after you have engaged in serious battle. Physics cannot be learned just by reading or listening, but only by thinking, writing and worrying.
Appendix A-B 227-244p.; Bibliography ccxlv p.; Index ccxlvi-ccxlviii p.
Keywords: Quantum theory